DNA methylation of a novel PAK4 locus influences ototoxicity susceptibility following cisplatin and radiation therapy for pediatric embryonal tumors - Brown, Austin L (Neuro Oncol, 2017)
BACKGROUND: Ototoxicity is a common adverse side effect of platinum chemotherapy and cranial radiation therapy; however, individual susceptibility is highly variable. Therefore, our objective was to conduct an epigenome-wide association study to identify differentially methylated cytosine-phosphate-guanine (CpG) sites associated with ototoxicity susceptibility among cisplatin-treated pediatric patients with embryonal tumors. METHODS: Samples were collected for a discovery cohort (n = 62) and a replication cohort (n = 18) of medulloblastoma and primitive neuroectodermal tumor patients. Posttreatment audiograms were evaluated using the International Society of Paediatric Oncology (SIOP) Boston Ototoxicity Scale. Genome-wide associations between CpG methylation and ototoxicity were examined using multiple linear regression, controlling for demographic and treatment factors. RESULTS: The mean cumulative dose of cisplatin was 330 mg/m(2) and the mean time from end of therapy to the last available audiogram was 6.9 years. In the discovery analysis of 435233 CpG sites, 6 sites were associated with ototoxicity grade (P < 5 × 10(−5)) after adjusting for confounders. Differential methylation at the top CpG site identified in the discovery cohort (cg14010619, PAK4 gene) was replicated (P = 0.029) and reached genome-wide significance (P = 2.73 × 10(−8)) in a combined analysis. These findings were robust to a sensitivity analysis evaluating other potential confounders. CONCLUSIONS: We identified and replicated a novel CpG methylation loci (cg14010619) associated with ototoxicity severity. Methylation at cg14010619 may modify PAK4 activity, which has been implicated in cisplatin resistance in malignant cell lines.